Scale‐free dynamics of core‐periphery topography. Issue 5 (29th December 2022) - Klar, Philipp; Çatal, Yasir; Langner, Robert; Huang, Zirui; Northoff, Georg
Abstract: The human brain's cerebral cortex exhibits a topographic division into higher‐order transmodal core and lower‐order unimodal periphery regions. While timescales between the core and periphery region diverge, features of their power spectra, especially scale‐free dynamics during resting‐state and their mdulation in task states, remain unclear. To answer this question, we investigated the 1/ f ‐like pink noise manifestation of scale‐free dynamics in the core‐periphery topography during rest and task states applying infra‐slow inter‐trial intervals up to 1 min falling inside the BOLD's infra‐slow frequency band. The results demonstrate (1) higher resting‐state power‐law exponent (PLE) in the core compared to the periphery region; (2) significant PLE increases in task across the core and periphery regions; and (3) task‐related PLE increases likely followed the task's atypically low event rates, namely the task's periodicity (inter‐trial interval = 52–60 s; 0.016–0.019 Hz). A computational model and a replication dataset that used similar infra‐slow inter‐trial intervals provide further support for our main findings. Altogether, the results show that scale‐free dynamics differentiate core and periphery regions in the resting‐state and mediate task‐related effects. Abstract : Scale‐free dynamics are investigated in the cerebral cortex's core‐periphery division in fMRI. Both rest and task states were assessed. We demonstrate that the brain's scale‐free dynamics are modulated by the task's periodicity in the infra‐slow band.